Profile and Programming Needs of Federal Offenders With Histories of Intimate Partner Violence. (October 2014) - Stewart, Lynn A.; Power, Jenelle
This study presents data on male perpetrators of domestic violence (DV) in the Correctional Service of Canada (CSC) using two samples: (a) a snapshot of all male offenders in CSC who had been assessed for DV ( n = 15, 166) and (b) a cumulative sample of male offenders in CSC from 2002-2010 who had been assessed as moderate or high risk for further DV ( n = 4, 261) DV offenders were compared to a cohort sample of non-DV offenders ( n = 4, 261). Analyses were disaggregated for Aboriginal and non-Aboriginal offenders. Results indicated that 40% of the federal male population had a suspected history of DV and were therefore screened in for in-depth DV risk assessment. Of these, 45% were assessed as moderate or high risk for future DV. DV offenders had higher risk and criminogenic need ratings, more learning disabilities, more mental health problems, and more extensive criminal histories than those without DV histories. Aboriginal DV offenders had high levels of alcohol dependence, suggesting a need for substance abuse treatment as part of DV programming. Most federal offenders with DV histories would be described as belonging to the Antisocial/Generalized Aggressive typology and, therefore, adhering to the Risk-Need-Responsivity principles of the effective correctional literature, cognitive-behavioral treatment that focuses on teaching skills of self-management, and changing attitudes supporting relationship violence would be recommended.